Severe α-Thalassemia Due to Compound Heterozygosity for Hb Adana (α59 Gly>Asp) (HBA1: c.179G > A) and Codon 127 (A > T) (HBA2: c.382A > T) in an Iranian Family. (3rd March 2020) - Azimi, Azam; Tahmasebi, Susan; Moradi, Keivan; Nejati, Parham; Alibakhshi, Reza
Abstract: We describe a novel compound heterozygous genotype which consists of two point mutations named Hb Adana ( HBA1 : c.179G>A) and codon 127 ( HBA2 : c.382A>T) in a Kurdish family with two girls affected with severe α-thalassemia (α-thal). Both patients (the proband and her sister) had a history of splenectomy during childhood. Although the proband had no blood transfusion history, her affected sister has had two blood transfusions so far. In conclusion, diagnosing and reporting new genotypes on the α-globin genes will improve our knowledge about complicated genotype-phenotype correlations in α-thal disorder.